2022
DOI: 10.1038/s41581-022-00586-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in kidney disease

Abstract: Extracellular vesicles are released by the majority of cell types and circulate in body fluids. They function as a long-distance cell-to-cell communication mechanism that modulates the gene expression profile and fate of target cells. Increasing evidence has established a central role of extracellular vesicles in kidney physiology and pathology. Urinary extracellular vesicles mediate crosstalk between glomerular and tubular cells and between different segments of the tubule, whereas circulating extracellular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
96
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 160 publications
0
96
0
Order By: Relevance
“…Extracellular vesicles (EVs) are small particles composed of a lipid bilayer secreted by all cell types under both physiological and pathological conditions. EVs display a relevant role in cell signaling and communication, thanks to the potential to transfer their molecular cargo (proteins, lipids and nucleic acids) and play a central function in kidney physiology and pathology [ 8 ]. In particular, EVs present in urine (uEVs) carry molecules that are characteristic of the epithelial cells present in the whole length of the urinary tract [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular vesicles (EVs) are small particles composed of a lipid bilayer secreted by all cell types under both physiological and pathological conditions. EVs display a relevant role in cell signaling and communication, thanks to the potential to transfer their molecular cargo (proteins, lipids and nucleic acids) and play a central function in kidney physiology and pathology [ 8 ]. In particular, EVs present in urine (uEVs) carry molecules that are characteristic of the epithelial cells present in the whole length of the urinary tract [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, uEVs are attracting increasing interest as potential urinary biomarkers and may represent a valuable source of information related to the state of renal tissue. Indeed, several data have highlighted the possible use of uEV cargo, including miRNAs, as biomarkers of kidney diseases [ 8 , 9 ], possibly reflecting their dysregulation in the renal tissue at various stages of DN [ 10 ]. In fact, miRNAs are relatively stable in tissue and biological fluids, particularly when carried by EVs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EVs composition also reflects their cellular origin, hence the importance of studying vesicles from different types of cells and under different physiological and pathological conditions [ 11 , 12 ]. The EV components can participate not only in various physiological processes such as homeostasis, inflammation, immunological interactions, and angiogenesis, but also in pathophysiological conditions involved in the development of cancer and metastasis, autoimmune diseases, and infections of various types [ 13 , 14 , 15 , 16 , 17 , 18 ]. EVs isolated from stem and endothelial progenitors have been tested in several disease models and shown to protect and/or repair kidney, nervous and heart tissue after injury, among other tissues and organs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To decrease and ultimately overcome the issue of variability among uEV studies, guidelines for reporting on isolation, characterization, and normalization have been developed by EV-TRACK (evtrack.org) and the Urinary Task Force of the International Society for Extracellular Vesicles [1,12]. Recent reviews have covered uEV biomarkers in other kidney diseases and kidney transplantation as well the therapeutic use of EVs [13,14]. Here, we review which tubular transporters have been identified and characterized in uEVs, how EVs may regulate tubular transporters, and whether uEV cargo may reveal disease mechanisms and serve as biomarkers for kidney disease and hypertension.…”
Section: Introductionmentioning
confidence: 99%